Institutional bypass and aid effectiveness in Africa - Michael Chasukwa; Dan Banik (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Many practical and action-oriented international roadmaps to improve the quality of aid and its delivery and impact on development-including the Paris Declaration, Accra Agenda for Action, and Busan Partnership-emphasize a more active involvement of domestic institutions and procedures. Despite widespread agreement among both donor and recipient countries on this issue, we find that a large amount of disbursed aid tends to bypass national institutional structures. This practice is often justified on grounds of high levels of political and administrative corruption and weak implementation capacity in recipient country bureaucracies. We examine how and to what extent multi- and bi-lateral development agencies bypass national and local government institutions while channeling aid and the impact of such practices on aid effectiveness in Africa. Based on an empirical study of project aid and budget support provided to Malawi by the World Bank, the African Development Bank, and the German Economic Group, we argue that earmarked funding, specialized procurement arrangements, and the proliferation of Project Management Units are among the mechanisms used to circumvent the involvement of national institutions. We conclude that while such practices may achieve short-term gains by displaying successful and visible "donorship," the long-term impact is more uncertain. The bypassing of local institutions results in the fragmentation of aid, a lack of coordination among aid industry actors, and a general weakening of policy space and domestic capacity to formulate and implement development policy.
Keywords: 330; Africa; aid; institutions; Malawi; policy space